Transformation of Teaching Practices Through Principal Leadership in Bekasi Middle Schools - Mesta Limbong, Mesta (LPPM Undiksha, 2024)
The principal is given more authority than teachers. One of them is to regulate and supervise the learning planning process, implementation, assessment and evaluation that must be carried out by teachers in the learning process. However, in fact, many teachers do not agree with the principal's policy in junior high schools. It was recorded that 54% considered that the principal only looked at the administration without paying attention to quality. Some other teachers considered that the principal only focused on bureaucracy, namely 48.88%. A study needs to be conducted with the gap between expectations and reality. So, the purpose of the study is to analyze and evaluate the performance of the principal and its influence on the implementation of the duties and responsibilities of teachers in schools. In this study, the method used was a quantitative type of Survey. With the number of respondents who assessed as many as 138 people from junior high schools spread across the city of Bekasi. The data collection technique used an instrument, and the instrument had been developed, validated and tested for reliability. The instrument was given to 138 junior high school teachers to be assessed. The instrument was distributed via a Google link. Each instrument item is assessed with a Likert scale, namely points 1-5, ranging from strongly disagree to strongly agree. The analysis technique with descriptive statistics assisted by SPSS Version 26.0 by looking at the mean, standard deviation, percentage and describing it in a bar chart. The results found that the principal was assessed as being in accordance with his duties and responsibilities as a principal. This finding confirms that the previous assessment was only valid in certain areas. The principal has carried out his duties well and is assessed as having provided a lot of input to teachers and not only paying attention to administration but also providing training on planning, how to compile materials, implementation, how to assess, conduct evaluations and provide training to junior high school teachers.